1997
DOI: 10.1046/j.1460-9592.1997.d01-94.x
|View full text |Cite
|
Sign up to set email alerts
|

Does thiopentone delay recovery in children premedicated with midazolam?

Abstract: This prospective, randomized trial of paediatric surgical outpatients, premedicated with oral midazolam, was designed to determine if an intravenous thiopentone induction of anaesthesia prolongs postoperative recovery compared to an inhalation induction with halothane. One hundred children, one to ten years of age, undergoing ENT surgical procedures of 30-60 min duration received midazolam 0.5 mg.kg-1 with atropine 0.03 mg.kg-1 and were randomized to either halothane (Group 1, n = 50) or a thiopentone inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In a double‐blind, placebo‐controlled study of paediatric outpatients induced with thiopental, early recovery time was prolonged 6.3 min, and discharge from hospital 59 min, by midazolam premedication (10). In a subsequent randomized trial of paediatric outpatients premedicated with midazolam, time to extubation was significantly prolonged by induction with thiopental compared with halothane, and children induced with thiopental were significantly more sedated in the first 30 min after anaesthesia (27). Animal and human studies have shown that intravenous midazolam and thiopental interact synergistically on induction of anaesthesia and it is possible that the same mechanism could prolong recovery times (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In a double‐blind, placebo‐controlled study of paediatric outpatients induced with thiopental, early recovery time was prolonged 6.3 min, and discharge from hospital 59 min, by midazolam premedication (10). In a subsequent randomized trial of paediatric outpatients premedicated with midazolam, time to extubation was significantly prolonged by induction with thiopental compared with halothane, and children induced with thiopental were significantly more sedated in the first 30 min after anaesthesia (27). Animal and human studies have shown that intravenous midazolam and thiopental interact synergistically on induction of anaesthesia and it is possible that the same mechanism could prolong recovery times (28,29).…”
Section: Discussionmentioning
confidence: 99%